Longitudinal rheumatoid factor autoantibody responses after SARS-CoV-2 vaccination or infection - Keijzer, Sofie; Oskam, Nienke; Ooijevaar-de Heer, Pleuni; Steenhuis, Maurice; Keijser, Jim B.D.; Wieske, Luuk; van Dam, Koos P.J.; Stalman, Eileen W.; Kummer, Laura Y.L.; Boekel, Laura; Kuijpers, Taco W.; ten Brinke, Anja; et al. (Frontiers in Immunology, 2024)
Background: Rheumatoid factors (RFs) are autoantibodies that target the Fc region of IgG, and are found in patients with rheumatic diseases as well as in the healthy population. Many studies suggest that an immune trigger may (transiently) elicit RF responses. However, discrepancies between different studies make it difficult to determine if and to which degree RF reactivity can be triggered by vaccination or infection.We quantitatively explored longitudinal RF responses after SARS-CoV-2 vaccination and infection in a well-defined, large cohort using a dual ELISA method that differentiates between true RF reactivity and background IgM reactivity. In addition, we reviewed existing literature on RF responses after vaccination and infection.Methods: 151 healthy participants and 30 RA patients were included to measure IgM-RF reactivity before and after SARS-CoV-2 vaccinations by ELISA. Additionally, IgM-RF responses after a SARS-CoV-2 breakthrough infection were studied in 51 healthy participants.Results: Published prevalence studies in subjects after infection report up to 85% IgM-RF seropositivity. However, seroconversion studies (both infection and vaccination) report much lower incidences of 2-33%, with a trend of lower percentages observed in larger studies. In the current study, SARS-CoV-2 vaccination triggered low-level IgM-RF responses in 5.5% (8/151) of cases, of which 1.5% (2/151) with a level above 10 AU/mL. Breakthrough infection was accompanied by development of an IgM-RF response in 2% (1/51) of cases.Our study indicates that de novo RF induction following vaccination or infection is an uncommon event, which does not lead to RF epitope spreading.